Influence of dual vitamin D therapy on the outcome in patients with moderate-to-severe acute anterior circulation cerebral infarction and vitamin D insufficiency - Wei, Jing; Cao, Wenying; Huang, Shuchun; Feng, Yuxing; Li, Cheng (Frontiers in Human Neuroscience, 2025)
ObjectiveTo observe whether dual vitamin D supplementation therapy can improve the prognosis of patients with moderate-to-severe anterior circulation acute cerebral infarction accompanied by vitamin D deficiency.MethodsA retrospective analysis was conducted on 36 patients with moderate-to-severe anterior circulation acute cerebral infarction accompanied by vitamin D deficiency. They were divided into a dual vitamin D supplementation therapy group and a control group. The 90-day mRS scores of the two groups of patients and the occurrence of hypercalcemia were compared.ResultsThe difference in the number of mRS 0–3 cases at 90 days was statistically higher in the dual vitamin D supplementation group than in the control group (P < 0.05). No hypercalcemia was observed in either group.ConclusionDual vitamin D supplementation improves outcomes in patients with moderate-to-severe anterior circulation acute cerebral infarction accompanied by vitamin D deficiency, and is relatively safe.